The Coronavirus pandemic and closed fitness clubs negatively affected members exercise habits - Gjestvang, Christina; Tangen, Elene Mauseth; Haakstad, Lene A. H. (Frontiers in Sports and Active Living, 2022)
Due to the Coronavirus pandemic, politicians enacted directions to reduce social interactions, including lockdown of fitness clubs. We aimed to investigate how this changed exercise habits of Norwegian gym members. Based on survey data, men and women ((≥18 years, n = 233, data collection from Aug. 2020 to Jan. 2021) were recruited to this study by an email-invitation from their fitness club chain or by Facebook advertisement. The participants reported on background variables (e.g., age, gender, total household income, occupation, and education), and exercise habits pre- and during social lockdown. Data were analyzed using independent or student t-test, chi-squared test, or McNemar's test, as appropriate. Home-based exercise (18.0% vs. 72.5%, p = <0.001), walking (49.8% vs. 65.2%, p = <0.001), and cycling (16.7% vs. 24.5%, p = 0.004) was more common during than pre-lockdown. Also, men (4.33 to 3.68 days/week, p =0.013) and women (4.20 to 3.79 days/week, p =0.001) reported a lower exercise frequency, and a shorter duration. Exercise frequency was lower in those with a BMI ≥25 than in those with BMI <25 (3.95 vs. 4.48 days/week, p = <0.007) pre-lockdown. High exercise attendees (≥3 sessions/week, 66.5%) reported a smaller decrease in exercise fre-quency (mean change: 0.06 vs. 1.24 days/week, p = <0.001) and duration (>60 min. per ses-sion: 33.0 vs. 3.8%, p = <0.001) than low exercise attendees during lockdown. Home-based exercise, walking, and cycling were most frequently reported during lockdown. Participants reported a small decrease in exercise duration and frequency compared with pre-lockdown. Closure of fitness clubs impacted low attendees more than high attendees.